Public Elementary School Teachers’ Perception of the Career Progression Scheme of the Department of Education in the Province of Albay - Millena, Herwena Joyce (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the awareness and perceptions of public elementary school teachers regarding the Expanded Career Progression System in the Schools Division of Legazpi City. Anchored in career development and motivation perspectives, particularly Life-Span, Life-Space theory, Social Cognitive Career Theory, and Herzberg’s Two Factor Theory, the study sought to describe teachers’ professional profile, assess their level of awareness of the system, and explore their perceptions, motivations, challenges, and prior preparation for promotion. An explanatory mixed-method design was employed, combining descriptive quantitative and qualitative approaches. The respondents were 97 permanent public elementary school teachers, with 10 participants included in the focus group discussion. Data were gathered through a structured questionnaire checklist, open-ended questions, and focus group discussion, then analyzed using frequency, percentage, weighted mean, Kendall’s Coefficient of Concordance, Mann-Whitney U Test, and thematic analysis. The findings showed that the respondents were generally professionally mature, predominantly female, mostly married, and largely engaged in graduate studies. Both Teacher I–III and Master Teacher I–II groups demonstrated high awareness of professional development, qualification standards, and merit and competence indicators under the Expanded Career Progression System, with no significant difference in awareness between the two groups. However, the qualitative findings revealed that teachers viewed career progression as both an opportunity for professional growth and a source of burden due to documentation demands, financial constraints, family responsibilities, workload, and policy-related concerns. The study concluded that while the system supports teacher development and advancement, its effective implementation depends on stronger institutional support, clearer policy dissemination, and more accessible professional development opportunities. The study aligns mainly with SDG 4 on Quality Education and also connects with SDG 8 and SDG 9 through teacher development, professional sustainability, and institutional strengthening. Its sustainability impact lies in supporting educational, institutional, policy, and socio-economic sustainability by informing more responsive and sustainable teacher promotion practices.
Keywords: Awareness; Career Progression; Elementary School Teacher; Expanded Career Progression System; Legazpi City; Merit and Competence; Professional Development; Qualification Standards; Teacher Perceptions